Molecular characterization and expression profiles of nicotinic acetylcholine receptors in the rice striped stem borer, Chilo suppressalis (Lepidoptera: Crambidae). (31st May 2016) - Xu, Gang; Wu, Shun‐Fan; Teng, Zi‐Wen; Yao, Hong‐Wei; Fang, Qi; Huang, Jia; Ye, Gong‐Yin
Abstract: Nicotinic acetylcholine receptors (nAChRs) are members of the cys‐loop ligand‐gated ion channel (cysLGIC) superfamily, mediating fast synaptic cholinergic transmission in the central nervous system in insects. Insect nAChRs are the molecular targets of economically important insecticides, such as neonicotinoids and spinosad. Identification and characterization of the nAChR gene family in the rice striped stem borer, Chilo suppressalis, could provide beneficial information about this important receptor gene family and contribute to the investigation of the molecular modes of insecticide action and resistance for current and future chemical control strategies. We searched our C. suppressalis transcriptome database using Bombyx mori nAChR sequences in local BLAST searches and obtained the putative nAChR subunit complementary DNAs (cDNAs) via reverse transcription polymerase chain reaction (RT‐PCR) and rapid amplification of cDNA ends methods. Similar to B. mori, C. suppressalis possesses 12 nAChR subunits, including nine α‐type and three β‐type subunits. Quantitative RT‐PCR analysis revealed the expression profiles of the nAChR subunits in various tissues, including the brain, subesophageal ganglion, thoracic ganglion, abdominal ganglion, hemocytes, fat body, foregut, midgut, hindgut and Malpighian tubules. Developmental expression analyses showed clear differential expression of nAChR subunits throughout the C. suppressalis life cycle. The identification of nAChR subunits in this study will provide a foundation for investigating the diverse roles played by nAChRs in C. suppressalis and for exploring specific target sites for chemicals that control agricultural pests while sparing beneficial species.